Pengembangan Potensi Lokal dan Penguatan Daya Saing Desa Jarangan Kecamatan Rejoso Kabupaten Pasuruan Melalui Inovasi Sosial, Ekonomi Kreatif, dan Transformasi Digital - Wiwin Ariesta; Billy M Syinwani; Salamatul Maulidiyah; Ali Husni; Wahyu Sasi Kirani (Fakultas Agama Islam Universitas Al Washliyah, 2025)
Jarangan Village is located in the Rejoso District of Pasuruan Regency. According to local government statistics, Jarangan Village is considered one of the least developed villages. However, in terms of its true potential, Jarangan Village possesses sufficient natural resources and human resources to become a thriving village. The community service team selected Jarangan Village as the location for this community service project, demonstrating the academics' commitment to village development. Several programs focused on developing local potential and strengthening competitiveness through social innovation, the creative economy, and digital transformation, all three of which are important but lacking in Jarangan Village, Rejoso District, Pasuruan Regency.